Isolation and Characterization of Water-soluble New Gingerlanosterol from Zingiber officinale Rhizomes - Chung, Ill-Min; Ali, Mohd; Ahmad, Ateeque (Asian Journal of Chemistry, 2016)
The rhizomes of Zingiber officinale after hydro-distillation of the essential oil have yielded one new compound Gingerlanosterol (Lanostan-3b, 25-diol-3b-D-glucopyranosyl 1,4-b-D-glucopyranoside) from waste water of ginger along with known hexanoic phosphate. The structure of the new compound was elucidated by 500 MHz NMR aided by EI-MS, IR spectra and chemical methods.